Situation Report: Czechoslovakia, 25 February 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Draft Guidance for the Sixth Five-Year Plan The Gypsies: The Bright and Dark Spots of a Limping Urbanization Reform of Military Education Courses at Institutes of Higher Education